Fostering Oral Skills in English through Gamification (2022)
ABSTRACT: This action research study conducted at a public institution in Medellin was aimed at evaluating the effectiveness of gamification strategies to foster eighth graders’ oral production in English by means of the mother tongue as a learning resource. Data were collected through a research journal, audio-recordings, a points format for the gamification activities, a focus group, and an interview with the cooperating teacher of the institution. Data analysis demonstrates the effectiveness of games to foster the students’ oral production in English because it provides students with opportunities to practice the target language in a safe environment. Evidence also shows that this strategy has additional benefits in students’ learning process such as competitiveness, confidence, and engagement. Regarding the mother tongue, it was found that it is useful for the students’ learning of the target language because it provides them with a tool for overcoming language difficulties. It is important to highlight that under different circumstances related to the context, the positive impact could have been higher.